2017
DOI: 10.1111/cid.12556
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant parameters and C‐reactive protein levels among patients with different obesity levels

Abstract: Clinical and radiographic peri-implant inflammatory parameters and serum CRP were significantly high in patients with severe form of obesity. Serum CRP levels correlated with peri-implant bleeding in obese patients. These findings are preliminary and long-term controlled trials are recommended to support these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Another remarkable finding in the present study is that the patients in T2DM and prediabetes groups had increased mean BMI that ranged from 29.6 to 37.2 kg/m 2 . Recent cross‐sectional and longitudinal data suggests that increased bodyweight is a significant systemic risk factor for both periodontal and peri‐implant tissue inflammation . In a recent study by Vohra and colleagues .…”
Section: Discussionmentioning
confidence: 99%
“…Another remarkable finding in the present study is that the patients in T2DM and prediabetes groups had increased mean BMI that ranged from 29.6 to 37.2 kg/m 2 . Recent cross‐sectional and longitudinal data suggests that increased bodyweight is a significant systemic risk factor for both periodontal and peri‐implant tissue inflammation . In a recent study by Vohra and colleagues .…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Similarly, in a recent cross-sectional study that assessed peri-implant outcomes in obese and non-obese patients, 27 showed that increased body weight is a predisposing factor for poor peri-implant outcomes that is possibly modified by c-reactive protein (a proinflammatory biomarker). Several recent studies reported that increased BMI is a modifying risk factor for periodontal tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
“…These radiographs were further scanned at 800 dots per inch using a scanner . Peri‐implant MBL was measured on the radiograph as the vertical distance from the crest of the alveolar bone to the platform of the dental implant …”
Section: Methodsmentioning
confidence: 99%